Ecosystem features determine seagrass community response to sea otter foraging. (September 2018) - Hessing-Lewis, Margot; Rechsteiner, Erin U.; Hughes, Brent B.; Tim Tinker, M.; Monteith, Zachary L.; Olson, Angeleen M.; Henderson, Matthew Morgan; Watson, Jane C.
Abstract: Comparing sea otter recovery in California (CA) and British Columbia (BC) reveals key ecosystem properties that shape top-down effects in seagrass communities. We review potential ecosystem drivers of sea otter foraging in CA and BC seagrass beds, including the role of coastline complexity and environmental stress on sea otter effects. In BC, we find greater species richness across seagrass trophic assemblages. Furthermore, Cancer spp. crabs, an important link in the seagrass trophic cascade observed in CA, are less common. Additionally, the more recent reintroduction of sea otters, more complex coastline, and reduced environmental stress in BC seagrass habitats supports the hypotheses that sea otter foraging pressure is currently reduced there. In order to manage the ecosystem features that lead to regional differences in top predator effects in seagrass communities, we review our findings, their spatial and temporal constraints, and present a social-ecological framework for future research. Graphical abstract: Highlights: Ecological features differ between seagrass beds in British Columbia and California. Seagrass community interactions influence predator effects in coastal systems. Ecological impacts of sea otter recovery are mitigated by seagrass resilience. Coastal management of top predators should include social-ecological linkages.